2018
DOI: 10.1101/367102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

acI Actinobacteria Assemble a Functional Actinorhodopsin with Natively-synthesized Retinal

Abstract: 18Freshwater lakes harbor complex microbial communities, but these ecosystems are often dominated by acI 19Actinobacteria from three clades (acI-A, acI-B, acI-C). Members of this cosmopolitan lineage are proposed 20 to bolster heterotrophic growth using phototrophy because their genomes encode actino-opsins (actR). 21This model has been difficult to experimentally validate because acI are not consistently culturable. In this 22 study, using genomes from single cells and metagenomes, we provide a detailed biosy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Many representatives are yellow-, orange- or red-pigmented due to various carotenoids; light-induced biosynthesis of these pigments was found in some strains [4]. Actinorhodopsins from bacteria of the phylum Actinobacteria with a putative proton pumping function were found predominantly in non-marine aquatic environments [5] and also among members of the family Microbacteriaceae [6, 7]. Genome-based phylogenies reconstructed from whole proteomes suggested that the family Microbacteriaceae is monophyletic [8].…”
Section: Full-textmentioning
confidence: 99%
See 1 more Smart Citation
“…Many representatives are yellow-, orange- or red-pigmented due to various carotenoids; light-induced biosynthesis of these pigments was found in some strains [4]. Actinorhodopsins from bacteria of the phylum Actinobacteria with a putative proton pumping function were found predominantly in non-marine aquatic environments [5] and also among members of the family Microbacteriaceae [6, 7]. Genome-based phylogenies reconstructed from whole proteomes suggested that the family Microbacteriaceae is monophyletic [8].…”
Section: Full-textmentioning
confidence: 99%
“…Nevertheless, available genomes belonging to the same phylogenetic cluster showed a similar pattern (). The so-called acl Actinobacteria , a group of bacteria with similar small genome sizes, showed a comparable pattern concerning the positions of these genes [7]. In contrast, genes predicted to encode complete rhodopsin/retinal systems in genomes of other members of the Microbacteriaceae shown in (i.e.…”
Section: Genomic Characterizationmentioning
confidence: 99%
“…Although we showed that A. minutum KNC T produced retinal, the genes responsible for its biosynthesis have not yet been identified. Among rhodopsin-possessing Actinobacteria, a lycopene cyclase encoded by the crtYc/Yd genes catalyzes the conversion of lycopene to β-carotene, which is then supplied for endogenous retinal (Dwulit-Smith et al, 2018). However, A. minutum has putative crtYe/Yf cluster genes, which encode C50 carotenoid epsilon cyclase (Krubasik et al, 2001;Netzer et al, 2010), not crtYc/Yd genes.…”
Section: Hypothesis Of An Unknown Retinal Biosynthetic Pathwaymentioning
confidence: 99%
“…ActR in Rhodoluna lacicola belonging to the acI lineage was active only if the exogenous retinal was supplied, suggesting that the cells lacked the retinal synthesis machinery [38]; in contrast, the Luna bacterium Candidatus Rhodoluna planktonica encodes a putative retinal-synthesizing system [39]. The biosynthetic route for retinal and carotenoids, which are necessary for the ActR function is elucidated in the acI lineage [40]. ActRs also contain the glycine residue for binding ketolated antenna carotenoids.…”
Section: Actinorhodopsin Proton Pumpsmentioning
confidence: 99%
“…The ecological roles of ActR in actinobacteria have been characterized mainly in a ubiquitous freshwater actinobacterial lineage, acI. All retinal biosynthesis pathway genes were transcribed, and ActR was most highly transcribed in a eutrophic lake [40]. A metatranscriptomic study of acI also reported the high expression of ActR and some transport proteins [75].…”
Section: Ecophysiological Roles Of Omega Rhodopsinsmentioning
confidence: 99%